SUNNI AND SHIA: AN APPROACH FROM ISLAMIC THOUGHT - Hamid, Rahmat; Idrus, Husni; Hasaruddin, Hasaruddin (Institut Agama Islam Negeri Bone, 2023)
This article aims to examine the differences and similarities between the Sunni-Shia groups that have caused these two major groups to unite. This article uses historical research methods, which analyzing the reality that occurred in the past and then implementing it in today's life. The data collection process is carried out by collecting all relevant sources or data needed, which focuses on scientific literature, historical documents and other writings related to the material on this discussion. As a result, there are differences that do not allow these two large groups to unite in theological matters, but when it comes to muamalah issues or interactions in socio-politics, this still allows for this union to occur.